Energy, Environment, and Sustainability: A Multi-criteria Evaluation of Countries - Aytekin , Ahmet (Strategic Planning for Energy and the Environment, 2022)
Energy, the environment, and sustainability are all strongly intertwined concerns. While humanity aims to spread the comfort and welfare it has achieved on a global scale, as well as to achieve more development and comfort through technological advances, it is caught in a stalemate caused by the world’s use of resources as if they are limitless, as well as irrevocable environmental damage. The major topic of this dilemma is energy. Using ARAT, CRITIC, SOWIA, CRADIS, and CODAS-Sort, this study aims to evaluate countries on the basis of energy, environment, and sustainability triangle. The results reveal that developed countries are in a better situation than developing and underdeveloped countries in terms of sustainable energy and environmental concerns. The Nordic countries notably lead the rankings and classification results. The primary reason for this is that Nordic countries have strong climate and energy policies. Given the limitations of fossil fuels, the fact that they’ll be exhausted in a few decades, and the environmental damage they cause, the development and effective use of renewable energy sources is considered a critical solution option. Because it appears that humanity will struggle to give up its existing level of comfort or lower its energy use. The importance of energy efficiency, diversification of renewable energy sources, raising societal awareness, unity in global sustainable environmental policies, aiding societies that are falling behind in achieving welfare and fighting poverty and focusing on energy savings emerge at this point. A strong will and community support will be necessary to adopt and implement these policies.